2019
DOI: 10.1016/j.jsha.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

An observational comparison of distal radial and traditional radial approaches for coronary angiography

Abstract: Background: Several studies have recently reported regarding feasibility and safety of distal transradial access (d-TRA) in the anatomical snuff-box (ASB); however, literature comparing it with the conventional TRA at the wrist (w-TRA) is sparse. This study compares the technical efficiency and safety of ASB and wrist approaches for TRA for coronary angiography (CAG) and evaluates the radial artery (RA) anatomy at these sites. Methods: Two hundred consecutive patients undergoing CAG via w-TRA or d-TRA (100 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…e overall catheterization/ puncture failure of dTRA included in this meta-analysis was higher than that of cTRA, but there was no statistically significant difference (4.3% VS 3.8%, P > 0.05), and the access time was prolonged in dTRA, but did not affect total procedure time. Bhambhani [11] performed distal radial artery cannulation in 100 patients and found access time in dTRA was progressively reduced, from 5.89 minutes in the first 25 cases to 2.47 minutes in the last 25 cases. Also, Lee [26] found that puncture time stabilized after approximately 150 distal radial artery punctures had been performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e overall catheterization/ puncture failure of dTRA included in this meta-analysis was higher than that of cTRA, but there was no statistically significant difference (4.3% VS 3.8%, P > 0.05), and the access time was prolonged in dTRA, but did not affect total procedure time. Bhambhani [11] performed distal radial artery cannulation in 100 patients and found access time in dTRA was progressively reduced, from 5.89 minutes in the first 25 cases to 2.47 minutes in the last 25 cases. Also, Lee [26] found that puncture time stabilized after approximately 150 distal radial artery punctures had been performed.…”
Section: Discussionmentioning
confidence: 99%
“…e meta-analysis showed similar catheterization/puncture failure between dTRA and cTRA, with no statistical significance (OR � 1.94, 95CI [0.97, 3.86], P � 0.06; I 2 � 78.5%, P < 0.001). We conducted a sensitivity analysis by removing outlier studies, heterogeneity was significantly reduced after excluding the studies by Bhambhani [11] and Koutouzis [17], and there was still no statistical difference (OR � 1.06, 95CI [0.69, 1.64], P � 0.788; I 2 � 38.2%, P � 0.114). e Egger test suggested the existence of publication bias among the studies (P � 0.015), so we used the trim and fill method to recalculate the effect size: the number of studies did not change, and there was still no statistical difference between them (OR � 1.927, 95CI [0.981, 3.785]), suggesting that the result was robust (see Figure 2).…”
Section: Meta-analysis Of Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies included 11 randomized control trials 4,5,17,[22][23][24][25][26][27][28][29] and the remainder were nonrandomized control or observational studies. 3,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The follow-up postcatheterization ranged from 1 day 28,35,36 to 6 months. 42 Sample sizes in the included studies ranged from 41 to 1307 patients (total: 9151 patients [DRA: 4,474; CRA: 4677]) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The ages of patients ranged from 50 to 72 years old, and studies included predominantly male patients [DRA: 72.4%; CRA: 70.0%]. Seven studies did not include any acute coronary syndrome (ACS) patients, 23,25,31,32,42,43,45 while one study included only ACS patients. 39 The rate of PCI varied amongst the studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%